Cardiopulmonary bypass for total aortic arch replacement surgery: A review of three techniques - Cui, Ying; Liu, Xinhao; Xiong, Jiyue; Tan, Zhaoxia; Du, Lei; Lin, Jing (Frontiers in Cardiovascular Medicine, 2023)
One treatment for acute type A aortic dissection is to replace the ascending aorta and aortic arch with a graft during circulatory arrest of the lower body, but this is associated with high mortality and morbidity. Maintaining the balance between oxygen supply and demand during circulatory arrest is the key to reducing morbidity and is the primary challenge during body perfusion. The aim of this review is to summarize current knowledge of body perfusion techniques and to predict future development of this field. We present three perfusion techniques based on deep hypothermic circulatory arrest (DHCA): DHCA alone, DHCA with selective cerebral perfusion, and DHCA with total body perfusion. DHCA was first developed to provide a clear surgical field, but it may contribute to stroke in 4%–15% of patients. Antegrade or retrograde cerebral perfusion can provide blood flow for the brain during circulatory arrest, and it is associated with much lower stroke incidence of 3%–9%. Antegrade cerebral perfusion may be better than retrograde perfusion during longer arrest. In theory, blood flow can be provided to all vital organs through total body perfusion, which can be implemented via either arterial or venous systems, or by combining retrograde inferior vena caval perfusion with antegrade cerebral perfusion. However, whether total body perfusion is better than other techniques require further investigation in large, multicenter studies. Current techniques for perfusion during circulatory arrest remain imperfect, and a technique that effectively perfuses the upper and lower body effectively during circulatory arrest is missing. Total body perfusion should be systematically compared against selective cerebral perfusion for improving outcomes after circulatory arrest.